2014
DOI: 10.1084/jem.21112oia68
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 loss in melanoma disrupts directional migration toward extracellular matrix cues

Abstract: Abbreviations used in this paper: 4-OHT, 4-hydroxy-tamoxifen; AMPK, AMPactivated protein kinase; ANOVA, analysis of variance; BRSK, brain-specific kinase; DN, dominant negative; FMI, forward migration index; MARK, microtubule affinity-regulating kinase; MMP, matrix metalloproteinase; NUAK, nua kinase; PDMS, polymethylsiloxane; qRT-PCR, quantitative RT-PCR; SIK, salt-inducible kinase; YAP, Yes-associated protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Small differences across a cell in the signaling pathways and protrusion dynamics are summed over time, leading to larger differences in cell movement and, ultimately, the haptotactic response. This might be a unique feature of slow moving mesenchymal cells such as fibroblasts, but it could also be a useful paradigm for studying directional migration in other contexts, such as in 1 dimensional migration, collective migration of epithelial cells or the invasion of tumor cells (Chan et al, 2014).…”
Section: Discussion a Working Model For Haptotaxismentioning
confidence: 99%
See 3 more Smart Citations
“…Small differences across a cell in the signaling pathways and protrusion dynamics are summed over time, leading to larger differences in cell movement and, ultimately, the haptotactic response. This might be a unique feature of slow moving mesenchymal cells such as fibroblasts, but it could also be a useful paradigm for studying directional migration in other contexts, such as in 1 dimensional migration, collective migration of epithelial cells or the invasion of tumor cells (Chan et al, 2014).…”
Section: Discussion a Working Model For Haptotaxismentioning
confidence: 99%
“…In that work, we demonstrated that loss of LKB1 and its direct downstream target MARK in melanoma leads to the loss of haptotaxis and of more invasive migration phenotypes (Chan et al, 2014). Tumor cells are known to ignore tissue boundaries, and failure to sense differences in the ECM could be one mechanism by which they ignore these boundaries.…”
Section: The Relevance Of Haptotaxis For Tumor Progression and Metastmentioning
confidence: 94%
See 2 more Smart Citations
“…Some effects of LKB1 are independent of AMPK and they are mediated via microtubule affinity-regulating kinase, synapses of the amphid defective kinase, and salt-inducible kinase. [18][19][20] Kidney fibrosis is the histologic manifestation of CKD. Kidney fibrosis is characterized by accumulation of matrix and inflammatory cells.…”
mentioning
confidence: 99%